2020
DOI: 10.1080/15623599.2020.1788759
|View full text |Cite
|
Sign up to set email alerts
|

Critical risk factors for implementing building information modelling (BIM): a Delphi-based survey

Abstract: Building information modelling (BIM) is one of the new technologies that, despite its perceived benefits and positive impacts towards the project objectives, has a very low level of adoption. The main problem with this issue may be attributed to several potential risk factors that disrupt the implementation of this technology. Previous research studies have identified various significant risk factors for implementing BIM technology, however, the relationships between these risk factors have not been evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…The Delphi technique was used to determine the importance of criteria and to screen key criteria before applying a multi-criteria decision-making method, which has been successfully implemented in similar studies concerning the classification of strategies within the R&M field (e.g., Ghazali et al, 2019;Hon et al, 2011Hon et al, , 2012. The Delphi technique is a structured process for collecting information to make decisions on qualitative issues Khoshfetrat et al, 2020;Olawumi & Chan, 2018). The main purpose of the Delphi technique is to obtain the most reliable set of expert opinions through a series of structured questionnaires with controlled feedback.…”
Section: Delphi Survey Methodsmentioning
confidence: 99%
“…The Delphi technique was used to determine the importance of criteria and to screen key criteria before applying a multi-criteria decision-making method, which has been successfully implemented in similar studies concerning the classification of strategies within the R&M field (e.g., Ghazali et al, 2019;Hon et al, 2011Hon et al, , 2012. The Delphi technique is a structured process for collecting information to make decisions on qualitative issues Khoshfetrat et al, 2020;Olawumi & Chan, 2018). The main purpose of the Delphi technique is to obtain the most reliable set of expert opinions through a series of structured questionnaires with controlled feedback.…”
Section: Delphi Survey Methodsmentioning
confidence: 99%
“…In the same vein, Ogunmakinde and Umeh (2018) acknowledged that BIM awareness has been growing steadily in the Nigerian construction industry but an understanding of its full potential is still lacking among construction professionals. However, other studies within the context of developing countries such as Nigeria (Babatunde et al, 2020); and Yemen (Gamil and Rahman, 2019); and other developing countries (Khoshfetrat et al, 2020) have identified lack of BIM awareness as still a challenge. However, despite the encouraging results around the higher levels of awareness during the design and construction stages, there is still a need of there is a need of translating this awareness into the actual usage and implementation of BIM across the entire project lifecycle.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Therefore, construction companies and the government should invest heavily on BIM technologies as it has great productivity increment potentials. This could include BIM software training (Khoshfetrat et al, 2020).…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…Regarding challenges, drawbacks, and barriers of BIM, one may mention complexity of BIM models, and BIM implementation lack of contractual requirement (Ahmed et al, 2014), lack of demand from contractors' side, lack of BIM awareness, contractors' lack of demand, lack of awareness to BIM benefits (Gerges et al, 2017), doubt on return of investment and lack of standardized tools and protocols, also; lack of BIM specialists and experts (McAuley et al, 2017), interoperability between software programs and issues in data ownership, inadequate BIM usage training (Park and KIM, 2017), lack of awareness to BIM benefits (Latiffi et al, 2016), client lack of interest, also; resistance to change construction culture (Sahil, 2016), top management lack of support, also, resistance to change construction culture (Ganah and John, 2015), high cost (Ismail et al, 2017), lack of sub-contractor's interest to use BIM (Hosseini et al, 2016), insufficient government support (Enshassi et al, 2016). Further, Okakpu et al (2020) and Khoshfetrat et al (2020) examined the challenges of BIM in terms of risk factors for implementation. The former concluded that socio-cultural, financial, technical, skill set, and contractual risks are the most important factors, and the latter found that lack of BIM comprehension, software training, and BIM skilled architects and engineers along with resistance to change are among the key risk elements.…”
Section: Bim Implementation For Micro Small and Medium-sized Enterprisesmentioning
confidence: 99%